FROM INNOVATION TO INNOVATIVE BUSINESS - Popa, Marina (SWorldJournal, 2023)
Innovation is the process of adapting from old to new, that would mean a 100 year difference or change from yesterday to today. It is the main source of economic growth and social and technological progress. In recent years, innovation-led economic growth